Improving productivity of Rex, Satin and Reza rabbits through selection - Bram Brahmantiyo; Y.C. Raharjo (Jurnal Ilmu Ternak dan Veteriner, 2011)
Selection based on weaning weight in Rex, Satin rabbits and their crosses was done to improve its productivity. Data from the base population (P0), selected population (G0) and an offspring of selected population (F1) were used to estimate heritability using nested analysis method (nested) and best linear unbiased prediction (BLUP). The value of heritability estimated of birth weight, weaning weight, 12 weeks body weight and 16 weeks body weight of Rex were 0.74±0.09, 0.93±0.05, 0.81±0.09 and 0.89±0.06, Satin were 0.96, 0.82±0.22, 0.93±0.40 and 0.97 and Reza were 0.96±0.27, 0.98, 0.86±0.40 dan 0.78, respectively. Increase in weaning weight on selected Rex, Satin rabbits and their corsses were 22.77 g (3.66%), 6.83 g (1.11%) and 65.29 g (10.67%). Key Words: Selection, Rabbit, Heritability, Weaning Weight